Effects of date palms (Phoenix dactylifera linn) and fig fruits (Ficus caricalinn) on rumen fermentation profiles and kinetics of cattle - Mohd Naspi, Nur Imanina Fakhira (2017)
This study was conducted to determine the effects of date palms (Phoenix dactylifera Linn) and fig fruits (Ficus carica Linn) on rumen fermentation profiles and kinetic of cattle. Grinded date palm fruit (Dabbas variety) and fig fruit (BMT6 variety) were used. The samples were then undergone nine types of proximate analysis which are dry matter, ash, crude protein, crude fibre, crude fat, neutral detergent fibre, acid detergent fibre, acid detergent lignin and energy determination. After the samples had undergone the nine proximate analysis, in vitro fermentation analysis was conducted to identify its digestibility and the rumen fermentation profiles and kinetic. In in vitro fermentation analysis, six treatments were used which were Blank rumen, Control 1 (Standard hay), Control 2 (Standard concentrate), Treatment 1 (Figs), Treatment 2 (Dates) and Treatment 3 (50% of Dates and 50% of Figs). Readings were recorded at 3, 6, 9, 12, 24, 48, 72 and 96 hours for total gas production with two replicates where rumen collection and in vitro fermentation analysis were done in two different weeks. The pH value was recorded at the beginning and the final time of the analysis. The media of the analysis were preserved after the final time of the analysis for VFA and ammonia determination and the samples that were not digested were determined in IVDMD. The result in proximate analysis shows significance difference (P<0.05) except for the crude fibre content. For the in vitro fermentation analysis, there is significance difference (P<0.05) between the treatments for final pH reading, IVDMD, and VFA content. The results of all the analysis showed positive effect and thus, showing that the date palms and fig fruits are good to be given as supplement feed for ruminants.